Needs Analysis of Cross Cultural Understanding-Based English Materials for Senior High School Students: Teachers’ Perception - Shella Monica; Novita Sari; Desy Seplyana; Meilida Eka Sari (STAI Hubbulwathan Duri, 2024)
The purpose of this study was to find out teachers’ perceptions toward the needs of Cross Cultural Understanding (CCU) based English materials for senior high schools students in South Sumatra, Indonesia. This needs analysis was conducted through survey with descriptive-analytical approach. Of 67 teachers were purposively selected to be the participants, only 6 teachers were given interviews. Questionnaire was distributed to all participants through Googleform on MGMP WA group. The percentages of teachers’ answer were automatically shown by Googleform results. Semi-structured interviews were given to 6 selected teachers by online and offline meetings. The results of interview were analyzed using Mile and Humberman’s steps of technique analysis namely data collection, data reduction, data presentation and conclusion. A triangulation technique was used to ensure the validity of the collected data. From the findings, it was recognized that lack of students’ knowledge of cultural diversity and inadequate CCU-based materials becomes the the biggest challenges faced by high school teachers in South sumatra. All teachers (100%) agree that CCU-based materials are needed in ELT, 66.7% of total respondents thought that the product could be used as media in promoting Indonesian culture to the next generation, while 33.3% thought that it could be used as media in increasing student’s reading interest. The findings lead to the conclusion that newly CCU-based material is highly needed for senior high schools. It can be the best alternative in increasing students’ knowledge of cultural diversity, reading interest and achiving the target of Indonesian cultural promotion.